Reimagining the Islamic Religious Education Curriculum in the Digital and Globalization Era - Rian Saputri; khoeron (JELCre - Journal of Education and Learning Creativity, 2025)
The development of digital technology and globalization has brought significant changes to the world of education, including the development of the Islamic Religious Education (PAI) curriculum. This condition requires the PAI curriculum to be adaptive, contextual, and relevant to the characteristics of students in the digital era without losing the essence of Islamic values. This research aims to examine the development of the PAI curriculum in the digital and global era, analyze the challenges and opportunities faced, and formulate innovations and strategies for implementing the PAI curriculum that are appropriate to current demands. This research uses a qualitative approach with library research methods through analysis of various scientific literature sources, including reputable international journals and relevant accredited national journals published within the last ten years. The results of the study indicate that the PAI curriculum needs to be dynamically developed by integrating the use of digital technology, strengthening religious literacy, and instilling the value of religious moderation. The challenges of the rapid flow of information and the influence of global values can be addressed through curriculum innovation and appropriate implementation strategies. Thus, the Islamic Religious Education curriculum in the digital and global era plays a strategic role in shaping students who are religious, critical, and have a global perspective.